Layers behind the moment. Nele Wynants, ed., “Media Archaeology and Intermedial Performance” (London: Palgrave Macmillan, 2019) - PREDESTRU, Mihai (Studia Universitatis Babeș-Bolyai Dramatica, 2019)
Stating that theatre is an evanescent art, the production “living” only for the brief interim between the audience’s entry and its departure, is a shibboleth commonly employed as an excuse for a certain lack of analytical rigor or objectivity in theatre criticism and history, both often approaching the phenomenon from either a literary or an anecdotal angle.